x + 2y = 5; y = – 2x – 2

(iv) x + 2y = 5; y = – 2x – 2

x + 2y = 5

X
5
3
1
Y
0
1
2
(X,Y)
(5,0)
(3,1)
(1,2)

Put, x = 5
5 + 2y = 5
2y = 5 – 5
2y = 0
y = 0/2
y = 0
Put, x = 3
3 + 2y = 5
2y = 5 – 3
2y = 2
y = 2/2
y = 1

Put, x = 1
1 + 2y = 5
2y = 5 – 1
2y = 4
y = 4/2
y = 2

y = – 2x – 2
X
0
1
2
Y
-  2
-4
-6
(X,Y)
(0,-2)
(1,-4)
(2,-6)

Put x = 0
y =  -2(0) – 2  
y = -2
Put x = 1
y = - 2(1) – 2
y = - 2 – 2
y = - 4
Put x = 2
y = - 2(2) -2
y =  - 4 – 2
y = - 6







 x = - 3 and y = 4 is the solution of given simultaneous equations.